Corpo e espiritualidade nas perspectivas cristã e em core energetics - Nunes, Marise Eterna (2020)
The integration of body and spirituality has emerged as a theme in humanistic and transpersonal approaches of psychology, which consider man as a whole when dealing with his physical, emotional, mental, and spiritual aspects altogether. This integrated notion of body coexists with other approaches, including the Christian perspective, present in religious traditions such as Catholicism. This study aimed to analyze how the process of self-knowledge and self-transformation obtained from the movement of the body brings about an awakening of spirituality in two approaches: 1) the Christian approach present in Catholicism, as observed in the celebrations of the group Oração Pastoral Missão Marca da Vitória, in Goiânia, GO, Brazil, based on the precepts of the Catholic Charismatic Renewal movement; 2) the psychotherapeutic approach, in Core Energetics, developed by the Greek physician, psychiatrist, and psychotherapist John Pierrakos and supported by the studies of the Austrian physician and psychoanalyst Wilhelm Reich, as observed in the classes of the formation course of body psychotherapists, organized by Rede Brasil of Core Energetics, in Brasília, DF, Brazil. This study intended to deepen the understanding of the awakening of spirituality through the body from a religious perspective and from a process of self-knowledge. In the present research, supported by extensive literature review, qualitative method was employed, and data were collected through field observation and interviews using a semi-structured questionnaire. It was hypothesized that there exists a distinction between the awakening of spirituality through the body in the Christian tradition, which attributes to the sacred the role of performing transformations, and in the process of self-knowledge, which assigns responsibility to the individual. In conclusion, to achieve the awakening of spirituality, regardless of how its origin is interpreted, it is necessary to have the individual¿s predisposition and effort